RELASI KOSAKATA FAUNA DALAM SAMPIRAN DAN ISI PANTUN â€œ1001 PANTUN PERIBAHASAâ€ KARYA SUDIADI - Novialdi, Hafiz; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe old Pantun Melayu also has a connection between sampiran and the contents of the pantun. Such relationships are like sound relationships and meaning relationships. This study discusses the interaction of sound images, interrelations of meaning images, interrelationships contained in the pantun, and interrelationships of language and matter. The interrelationship is based on the vocabulary of fauna contained in the sampun of the book "1001 Pantun Per Pro" by Sudiadi. This research was conducted on 102 fauna vocabulary found in 359 rhymes. Then after the fauna vocabulary data was obtained, then it was tested on 10 respondents taken randomly. There are as many as 100 fauna vocabulary found in 339 rhymes that researchers found to have sound image interrelationships in the rhyme, 16 fauna vocabulary which have meaningful image relations contained in 22 rhymes, and 7 rhyme fruits that have inter -relations in the rhyme. Then from the questionnaire given to respondents found 10 fauna vocabulary in terms of language, and also 10 fauna vocabulary in terms of objects that are less than or equal to 5 who know.Keywords: Ecolinguistics, Pantun, Sampiran Pantun, Vocabulary of FaunaÂ